Structural, Non-Covalent Interaction, and Natural Bond Orbital Studies on Bromido-Tricarbonyl Rhenium(I) Complexes Bearing Alkyl-Substituted 1,4-Diazabutadiene (DAB) Ligands - Reza Kia; Azadeh Kalaghchi (Crystals, 2020)
The synthesis, characterization, structural and computational studies of Re(I) tricarbonyl bromo complexes bearing alkyl-substituted 1,4-diazabutadiene ligands, [Re(CO)3(1,4-DAB)Br], where 1,4-DAB = N,N-bis(2,4-dimethylbenzene)-1,4-diazabutadiene, 2,4-Me2DAB (1); N,N-bis(2,4-dimethylbenzene)-2,3-dimethyl-1,4-diazabutadiene, 2,4-Me2DABMe (2); N,N-bis(2,4,6-trimethylbenzene)-1,4-diazabutadiene, 2,4,6-Me3DAB (3); and N,N-bis(2,6-diisopropylbenzene)-1,4-diazabutadiene, 2,6-ipr2DAB (4) are reported. The complexes were characterized by different spectroscopic methods such as FT-IR, 1H-NMR, 13C-NMR, and elemental analyses and their solid-state structures were confirmed by X-ray diffraction. In each complex, the Re(I) centre shows a distorted octahedral shape with a facial geometry of carbonyl groups. The gas phase geometry of the complexes was identified by density functional theory. Interesting intermolecular n…π* interactions of complexes 1 and 3 were investigated by non-covalent interaction index (NCI), and natural bond orbital (NBO) analyses. The intramolecular n…σ*, σ…π*, π…σ* interactions were also studied in complexes 3 and 4.